Research on the implementation status and improvement strategies of cloud classroom personality teaching in elementary schools - Li Xiang Mao; Sri Leny (Jurnal Inovasi Teknologi Pendidikan, 2023)
Currently, the development of students' personality and the cultivation of innovative talents are regarded as an important task of education for each country, the personalized teaching has become the goal of the new curriculum reform in China. With the continuous development of cloud computing technology, network cloud platform education resources are being used more and more in the teaching process, the " personalized teaching of the cloud classroom" in primary schools has gradually become the highlight for the reform and research of the basic education in Nanjing. Since it was officially launched in 2010, Nanjing has 1380 high-quality courses in the cloud classroom, trained 775 backbone teachers, explored new teaching models, accumulated a wealth of teaching cases. At the same time, in the implementation process, it also faces many problems and challenges related to educational concept, technology and application. This study use the literature design and case study method to define the relevant conceptss in analyze the teaching. The result of this study shown that the use of cloud classroom teaching can provide teachers visual expression tools for the smooth implementation of teaching, reduce the teaching burden of teachers, and provide students with a teaching environment rich in pictures and texts, stimulate learning interest and improve learning efficiency.